(untitled) (Anclajes, 2018)
It aims at analyzing the literary expression of masculinity and emotions, and their reception, in Perros que ladran en el sótano (2012), Olga Merino’s third novel. With such purpose, we’ll review her journalistic work, formal and thematic issues of this work as well as topics related to gender and sexuality, those which better illustrate its ideological significance. It can be argued that the tapestry reconstructed by Merino in her third fiction reflects historically a Spanish cultural tradition, but also predetermines particular modes of seeing and feeling masculinity.